Efecto de la albahaca (Ocimum basilicum) en sustitución al lúpulo en la elaboración de una cerveza artesanal - Valencia Borja, Abel Leonardo (2022)
The craft beer market is constantly changing and this project aims to provide a new alternative in the craft beer market to contribute to the economic growth of the country. The objective of this research is to evaluate the effects of basil (ocimum basilicum) as a substitute for hops in the production of craft beer